Venation patterns of neotropical blueberries (Vaccinieae: Ericaceae) and their phylogenetic utility - Pedraza-Peñalosa, Paola; Salinas, Nelson R.; Wheeler, Ward C. (Phytotaxa, 2013)
The description of venation patterns in neotropical Vaccinieae has been problematic because of the lack of an operational definition. Moreover, the underlying homologies remain unknown across and within lineages, thus precluding the use of venation characters in phylogenetic analyses. Venation patterns are often obscured in herbarium and living specimens due to the characteristic coriaceous and thick nature of Ericaceae leaves. Therefore, to obtain an unobstructed view of the veins, leaf clearings of 16 putative generic lineages of Vaccinieae were prepared and described. The main venation patterns were then defined and traditional definitions of venation were discussed in the light of the observed patterns. Selected characters were scored and the evolution of venation characters was discussed using a phylogenetic framework derived from molecular data analyzed under Maximum Likelihood. Venation descriptions and photographs are provided for 33 species.